Evaluation of PCR on bronchoalveolar lavage fluid for diagnosis of invasive aspergillosis: a bivariate metaanalysis and systematic review. - Wenkui Sun; Ke Wang; Wei Gao; Xin Su; Qian Qian; Xin Lu; Yong Song; Yaling Guo; Yi Shi (PLoS ONE)
Background Nucleic acid detection by polymerase chain reaction (PCR) is emerging as a sensitive and rapid diagnostic tool. PCR assays on serum have the potential to be a practical diagnostic tool. However, PCR on bronchoalveolar lavage fluid (BALF) has not been well established. We performed a systematic review of published studies to evaluate the diagnostic accuracy of PCR assays on BALF for invasive aspergillosis (IA). Methods Relevant published studies were shortlisted to evaluate the quality of their methodologies. A bivariate regression approach was used to calculate pooled values of the method sensitivity, specificity, and positive and negative likelihood ratios. Hierarchical summary receiver operating characteristic curves were used to summarize overall performance. We calculated the post-test probability to evaluate clinical usefulness. Potential heterogeneity among studies was explored by subgroup analyses. Results Seventeen studies comprising 1191 at-risk patients were selected. The summary estimates of the BALF-PCR assay for proven and probable IA were as follows: sensitivity, 0.91 (95% confidence interval (CI), 0.79-0.96); specificity, 0.92 (95% CI, 0.87-0.96); positive likelihood ratio, 11.90 (95% CI, 6.80-20.80); and negative likelihood ratio, 0.10 (95% CI, 0.04-0.24). Subgroup analyses showed that the performance of the PCR assay was influenced by PCR assay methodology, primer design and the methods of cell wall disruption and DNA extraction. Conclusions PCR assay on BALF is highly accurate for diagnosing IA in immunocompromised patients and is likely to be a useful diagnostic tool. However, further efforts towards devising a standard protocol are needed to enable formal validation of BALF-PCR.